Strategi Pengembangan UMKM Berbasis Digitalisasi: Implementasi Program Pelatihan dan Pendampingan Digital Marketing untuk Meningkatkan Daya Saing UMKM kota Balikpapan - Amir Iskandar; Sani Gazali; Adi Prihanisetyo (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2025)
Micro, Small and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economy with a contribution of 61.07% to GDP and able to absorb 97% of the national workforce. However, the digitalization era requires MSMEs to adapt to digital technology to maintain competitiveness. This study aims to analyze the effectiveness of digital marketing training and mentoring programs in improving digital literacy of UMKM practitioners in Balikpapan City. The research method uses an experimental approach with pre-test and post-test design on 25 UMKM practitioners. The research instrument was a questionnaire with 30 multiple choice questions measuring three aspects: basic knowledge of digitalization, understanding of digital marketing, and ability to use social media and marketplaces. The training program was conducted for one day with materials covering UMKM digitalization, digital marketing fundamentals, social media marketing, and marketplace usage. The results showed significant improvements in all aspects: basic digitalization knowledge increased by 59% (from 50.4 to 80.2), digital marketing understanding increased by 71% (from 43.4 to 74.4), and social media and marketplace capabilities increased by 46% (from 59.2 to 86.2). Beginner category participants showed the most significant progress with an average increase of 86%. The program success rate reached 92% with 23 out of 25 participants successfully achieving satisfactory scores. This program proves the effectiveness of digital marketing training in improving UMKM digital literacy and provides a foundation for sustainable digital transformation.